Pengaruh Pemberian Pupuk Cair Urine Sapi terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) pada Lahan Podsolik Merah Kuning - Nur Hafizah; Rusmadi Rusmadi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2015)
Yellow red podsolic soil has the potential for crop cultivation. The problems faced in the development of plant cultivation on yellow red podsolic land are very low pH and nutrient poor. The purpose of this study was (i) to know the effect of giving cow urine liquid fertilizer to the growth and yield of cucumber plants on yellow red podsolic land (ii) to obtain the best dose of cow urine liquid fertilizer on the growth and yield of cucumber plants on red yellow podzolic fields. The study was conducted in Mantimin Village, Batu Mandi Subdistrict, Balangan Regency in June - July 2011. This study used a Randomized Block Design (RBD), with 5 treatments and 4 replications, so that all of them were 20 experimental units. Each experimental unit consists of 4 plants. Factors are tested for cow urine liquid dosage, u0 = 0 cc / liter of water / plot, u1 = 25 cc of water per plot, u2 = 50 cc / liter of water / plot, u3 = 75 cc / liter of water / plot, and u4 = 100 cc / liter of water / plot. The results showed that the treatment of doses of cow urine fertilizer significantly affected plant height variables aged 14 days after planting (HST), number of leaves aged 14 HST, number of branches, age of plants at flowering, number of fruit crops and weight of fruit at the best dose is 100 cc / liter of water / plot (u4) and does not show any influence on plant height at 28 HST.